Platelets in Wound Healing: What Happens in Space? - Locatelli, Laura; Colciago, Alessandra; Castiglioni, Sara; Maier, Jeanette A. (Frontiers in Bioengineering and Biotechnology, 2021)
Beyond their fundamental role in hemostasis, platelets importantly contribute to other processes aimed at maintaining homeostasis. Indeed, platelets are a natural source of growth factors and also release many other substances - such as fibronectin, vitronectin, sphingosine 1-phosphate - that are important in maintaining healthy tissues, and ensuring regeneration and repair. Despite the thrombotic events documented in astronauts, some in vivo and in vitro studies demonstrate that microgravity affects platelets’ number and function, thus increasing the risk of hemorrhages and contributing to retard wound healing. Here we provide an overview about events linking platelets to the impairment of wound healing in space, also considering other factors, besides weightlessness, that might impair platelets, such as exposure to radiation and psychological stress. In the end we discuss the possibility of utilizing platelet rich plasma as a tool to treat skin injuries eventually occurring during space missions.